การวัดระยะทางแบบสามมิติด้วยภาพในการนำร่องแบบทันการสำหรับระบบอากาศยานไร้คนขับประเภทขึ้นลงแนวดิ่ง - นิค จำนง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This work proposes a method for implementing a localization technique that uses an omni directional camera in addition to other sensors to help UAV navigate in the environment where GPS data becomes unreliable. The proposed method uses computer vision techniques to extract information from series of live images acquired by the omni directional camera installed onboard the UAV. The extracted information is then combined with measurements from other sensors including IMU and GPS to determine the position of the UAV. The objective is to achieve localization with more robustness and accuracy than using the GPS alone. The proposed method is implemented and preliminary results are presented